1991
DOI: 10.1093/ajh/4.11.909
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide and Brain Natriuretic Peptide Coexist in the Secretory Granules of Human Cardiac Myocytes

Abstract: To elucidate the intracellular localization of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) in human cardiac myocytes, an immunocytochemical study was carried out by a double immunogold technique using antisera highly specific for ANP and BNP. Surgical and autoptic tissue specimens of human heart were studied. In the atrial myocytes, ANP was localized in almost all of the secretory granules, whereas BNP was colocalized with ANP in some of the granules. Although very few secretory granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 0 publications
1
47
0
4
Order By: Relevance
“…This observation confirms previous reports on the time course of ANP secretion in vitro 25,29,30 and is consistent with rapid depletion of a "stretch-sensitive pool" of ANP. 29 -31 ANP and BNP have been colocalized in human, 32 rat, 33 and porcine 34 cardiac myocytes, and it may be that some of the observed increases in plasma ANP, NT-proBNP, and BNP in the present study are derived from corelease from a single class of cardiac myocyte granule. Thus, it is possible that the concept of a readily releasable pool of atrial ANP for stretch-induced release 29,30 may also apply to colocalized BNP within secretory granules.…”
Section: Discussionmentioning
confidence: 54%
“…This observation confirms previous reports on the time course of ANP secretion in vitro 25,29,30 and is consistent with rapid depletion of a "stretch-sensitive pool" of ANP. 29 -31 ANP and BNP have been colocalized in human, 32 rat, 33 and porcine 34 cardiac myocytes, and it may be that some of the observed increases in plasma ANP, NT-proBNP, and BNP in the present study are derived from corelease from a single class of cardiac myocyte granule. Thus, it is possible that the concept of a readily releasable pool of atrial ANP for stretch-induced release 29,30 may also apply to colocalized BNP within secretory granules.…”
Section: Discussionmentioning
confidence: 54%
“…[11][12][13][14] Atrial natriuretic peptide (ANP) and BNP have similar properties, but the half-life of BNP is five-to six-fold longer, and BNP is mainly secreted from the ventricles in the heart, whereas ANP mainly derives from the atria. [15][16][17] There is great interest in the diagnostic use of BNP for detection of ventricular dysfunction. Several authors have suggested that determination of BNP levels could be used as a screening technique for cardiac disease.…”
mentioning
confidence: 99%
“…In contrast, the main production and secretion of BNP is from the heart ventricles (Mukoyama et al 1991), primarily the left (Yasue et al 1994), although this peptide is expressed in small amounts in the atrium. Different studies have shown that both ANP and BNP are stored in the atrium in the same granules and that both are secreted into the circulation under similar conditions (Nakamura et al 1991;Thibault et al 1992;Takemura et al 1998).…”
mentioning
confidence: 99%